Wetland vegetation changes in response to climate change and human activities on the Tibetan Plateau during 2000–2015 - Chen, Yuhan; Sun, Lu; Xu, Jiangqi; Liang, Boyi; Wang, Jia; Xiong, Nina (Frontiers in Ecology and Evolution, 2023)
The Tibetan Plateau, known as the third pole, is the highest plateau in the world. It has a large number of wetlands, which are important ecological security barriers and plays an important role in mitigating global climate change. This paper employed breaks for additive seasonal and trend (BFAST) algorithm for the mutation detection of the monthly normalized difference vegetation index (NDVI). In addition, correlation analysis and residual analysis were used to study the response of climate change and human activities to NDVI of alpine wetland vegetation in the Tibetan Plateau during 2000-2015. The results indicate that the climate in alpine wetland presented the trend of dry heat development with the increase of NDVI. The wetland NDVI was greatly affected by temperature factor. The temperature had an insignificant time lag effect on plant growth, and precipitation and solar radiation had time lag effect on NDVI. Additionally, human activities have a slight positive impact on the wetland. This study explored, for the first time, the NDVI variations of the dynamic wetland and their correlations with temperature, precipitation and solar radiation.